A Comparative Study of the Inhibitors of Fibrinolysis in Human, Dog and Rabbit Blood - Gallimore, M. J; Nulkar, M. V; Shaw, JTB (Thrombosis and Haemostasis, 1965)
Comparison of sera from dog, rabbit and man shows that dog serum contains most fibrinolytic inhibitor and human serum least. The inhibitors are potentiated by a variety of inorganic salts, of which sodium chloride is most effective. Euglobulin fractions precipitated from rabbit and human plasma at pH 5.3 contain small amounts of inhibitory material, whereas little remains in the corresponding dog euglobulin or in euglobulins from all three species when precipitated at pH 6.0. The potentiation of fibrinolytic inhibitors by sodium chloride differs between the three species, suggesting that their composition is not identical. Chloroform extraction removes a proportion of the inhibitory material from each serum.